Analisis Mura’at Al-Nazhir dalam Surah Al-Waqi’ah - Annisa Annisa; Citra Sukma Ayu; Yuyun Jelita Jabat; Harun Al-Rasyid (STIKes Ibnu Sina Ajibarang, 2025)
Mura'at al-Nazhiris a concept that refers to the harmony between wording and meaning, which plays a crucial role in the clarity of communication and rhetorical appeal. This concept encompasses the use of precise language, appropriate word choice, and effective sentence structure to optimally convey messages. This research aims to explore the role ofMura'at al-Nazhirin deepening the understanding ofBalaghah, particularly in the interpretation of classical texts. The methodology employed is a literature study using a qualitative approach, analyzing various classical and contemporary sources in the field ofBalaghah. The findings indicate that the application of Mura'at al-Nazhirnot only enhances the clarity and rhetorical appeal of texts but also provides interpretative depth that enables readers to understand the cultural and historical context behind the texts. This research is expected to make a significant contribution to the study of Arabic rhetoric and open up opportunities for further research on the application ofMura'at al-Nazhirin various literary contexts.